The Impact of Competence, Motivation and Discipline on Employee’s Performance: A Case Study of PT PLN (Persero) UPT Palembang - Syarifah, Ulfi Fathiyyatus; Asiati , Diah Isnaini; Moelyatie, Trisniarty Adjeng (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2023)
The formulation of the problem in this study is how the influence of Competence, Motivation and Work Discipline on Employee Performance at PT PLN (Persero) The formulation of the problem in this study is how the influence of Competence, Motivation and Work Discipline on Employee Performance at PT PLN (Persero) UPT Palembang. The research objective is to determine the effect of Competence, Motivation and Work Discipline on Employee Performance at PT PLN (Persero) UPT Palembang. This research was developed with an associative design. There are four variables which, as a whole, are set into 12 indicators. The research sample was 124 out of 170 PT PLN (Persero) UPT Palembang employees, taken by random cluster sampling. The data used in this study is primary data collected using a questionnaire. The analysis technique used is multiple linear regression. The results of multiple linear regression testing show a significant influence of Competence, Motivation and Work Discipline on employee performance at PT PLN (Persero) UPT Palembang. Partially shows that competence has a positive and insignificant effect on employee performance. In contrast, Motivation and Work Discipline positively and significantly affect the Performance of PT PLN (Persero) UPT Palembang Employees.